Individual Differences in Working Memory Capacity Modulates Semantic Negative Priming from Single Prime Words - Ortells, Juan J.; Noguera, Carmen; Álvarez, Dolores; Carmona, Encarna; Houghton, George (Frontiers in Psychology, 2016)
The present study investigated whether semantic negative priming from single prime words depends on the availability of cognitive control resources. Participants with high vs. low working memory capacity (as assessed by their performance in complex span and attentional control tasks) were instructed to either attend to or ignore a briefly presented single prime word that was followed by either a semantically related or unrelated target word on which participants made a lexical decision. Individual differences in working memory capacity (WMC) mainly affected the processing of the ignored primes, but not the processing of the attended primes: While the latter produced reliable positive semantic priming for both high- and low-WMC participants, the former gave rise to reliable semantic negative priming only for high WMC participants, with low WMC participants showing the opposite positive priming effect. The present results extend previous findings in demonstrating that (a) single negative priming can reliably generalize to semantic associates of the prime words, and (b) a differential availability of cognitive control resources can reliably modulate the negative priming effect at a semantic level of representation.